Identification of key genes involved in flavonoid and terpenoid biosynthesis and the pathway of triterpenoid biosynthesis in Passiflora edulis - Yi XU; Dong-mei HUANG; Fu-ning MA; Liu YANG; Bin WU; Wen-ting XING; Pei-guang SUN; Di CHEN; Bing-qiang XU; Shun SONG (Journal of Integrative Agriculture, 2023)
Passion fruit (Passiflora edulis Sims) is a vine of the Passiflora genus in the Passifloraceae family. The extracted components include flavonoids and terpenoids, which have good anti-anxiety and anti-inflammatory effects in humans. In this study, we analyzed the transcriptomes of four tissues of the ‘Zixiang’ cultivar using RNA-Seq, which provided a dataset for functional gene mining. The de novo assembly of these reads generated 96 883 unigenes, among which 61 022 unigenes were annotated (62.99% yield). In addition to its edible value, another important application of passion fruit is its medicinal value. The flavonoids and terpenoids are mainly derivatives of luteolin, apigenin, cycloartane triterpenoid saponins and other active substances in leaf extracts. A series of candidate unigenes in the transcriptome data that are potentially involved in the flavonoid and terpenoid synthesis pathways were screened using homology-based BLAST and phylogenetic analysis. The results showed that the biosynthesis of triterpenoids in passion fruit comes from the branches of the mevalonate (MVA) and 2-C-methyl-D-erythritol 4-phosphate/1-deoxy-D-xylulose 5-phosphate (MEP/DOXP) pathways, which is different from the MVA pathway that is used in other fruit trees. Most of the candidate genes were found to be highly expressed in the leaves and/or flowers. Quantitative real-time PCR (qRT-PCR) verification was carried out and confirmed the reliability of the RNA-Seq data. Further amplification and functional analysis of these putative unigenes will provide additional insight into the biosynthesis of flavonoids and terpenoids in passion fruit.